Sustained Intracellular Acidosis Triggers the Na + /H + Exchager-1 Activation in Glutamate Excitotoxicity - Lee, Bo Kyung; Jung, Yi-Sook (Biomolecules & therapeutics, 2017)
The Na⁺/H⁺ exchanger-1 (NHE-1) is a ubiquitously expressed pH-regulatory membrane protein that functions in the brain, heart, and other organs. It is increased by intracellular acidosis through the interaction of intracellular H⁺ with an allosteric modifier site in the transport domain. In the previous study, we reported that glutamate-induced NHE-1 phosphorylation mediated by activation of protein kinase C-β (PKC-β) in cultured neuron cells via extracellular signal-regulated kinases (ERK)/p90 ribosomal s6 kinases (p90RSK) pathway results in NHE-1 activation. However, whether glutamate stimulates NHE-1 activity solely by the allosteric mechanism remains elusive. Cultured primary cortical neuronal cells were subjected to intracellular acidosis by exposure to 100 μM glutamate or 20 mM NH₄Cl. After the desired duration of intracellular acidosis, the phosphorylation and activation of PKC-β, ERK1/2 and p90RSK were determined by Western blotting. We investigated whether the duration of intracellular acidosis is controlled by glutamate exposure time. The NHE-1 activation increased while intracellular acidosis sustained for 〉3 min. To determine if sustained intracellular acidosis induced NHE-1 phosphorylation, we examined phosphorylation of NHE-1 induced by intracellular acidosis by transient exposure to NH₄Cl. Sustained intracellular acidosis led to activation and phosphorylation of NHE-1. In addition, sustained intracellular acidosis also activated the PKC-β, ERK1/2, and p90RSK in neuronal cells. We conclude that glutamate stimulates NHE-1 activity through sustained intracellular acidosis, which mediates NHE-1 phosphorylation regulated by PKC-β/ERK1/2/p90RSK pathway in neuronal cells.